Hospital Based Health Technology Assessment: an example from Siena - Manzi, Pietro; Barberini, Pietro; Dori, Fabrizio (Farmeconomia. Health Economics and Therapeutic Pathways, 2015)
The Health Technology Assessment (HTA) has emerged in recent years as a useful tool in healthcare decision-making. It is a multidisciplinary process that summarizes information about the medical, social, economic and ethical issues related to the use of a health technology and provides evidence-based information on how to allocate resources. The experience of Siena University Hospital is an example of multidisciplinary hospital-based HTA. In the present paper we summarize the organization of HTA commission and the assessment methodology of the purchase, rental or sale of medical equipment and medical devices. Furthermore we illustrate the data concerning the commission activities in 2013.